Navigating the Shoals of Joint Infringement, Indirect Infringement, and Territoriality Doctrines: A Comparative Analysis of Chinese and American Patent Laws - Kene, Gautam V.; King, Patrick E.; Lau, Timothy T. (Columbia Journal of Asian Law, 2012)
The patent laws of both China and the United States have joint infringement and indirect infringement doctrines, and both countries obey territoriality principles in applying intellectual property rights (IPRs). These doctrines and principles, however, are construed and applied differently on the two sides of the Pacific. This Article compares and contrasts the two legal regimes and identifies potentially significant gaps in patent coverage for patented but divisible systems that are practiced in separate legal jurisdictions.